Overcoming the challenges of developing an intranasal diazepam rescue therapy for the treatment of seizure clusters. (22nd February 2021) - Cloyd, James; Haut, Sheryl; Carrazana, Enrique; Rabinowicz, Adrian L.
Abstract: Seizure clusters must be treated quickly and effectively to prevent progression to prolonged seizures and status epilepticus. Rescue therapy for seizure clusters has focused on the use of benzodiazepines. Although intravenous benzodiazepine administration is the primary route in hospitals and emergency departments, seizure clusters typically occur in out‐of‐hospital settings, where a more portable product that can be easily administered by nonmedical caregivers is needed. Thus, other methods of administration have been examined, including rectal, intranasal, intramuscular, and buccal routes. Following US Food and Drug Administration (FDA) approval in 1997, rectal diazepam became the mainstay of out‐of‐hospital treatment for seizure clusters in the United States. However, social acceptability and consistent bioavailability present limitations. Intranasal formulations have potential advantages for rescue therapies, including ease of administration and faster onset of action. A midazolam nasal spray was approved by the FDA in 2019 for patients aged 12 years or older. In early 2020, the FDA approved a diazepam nasal spray for patients aged 6 years or older, which has a different formulation than the midazolam nasal product and enhances aspects of bioavailability. Benzodiazepines, including diazepam, present significant challenges in developing a suitable intranasal formulation. Diazepam nasal spray contains dodecyl maltoside (DDM) as an absorption enhancer and vitamin E to increase solubility in an easy‐to‐use portable device. In a Phase 1 study, absolute bioavailability of the diazepam nasal spray was 97% compared with intravenous diazepam. Subsequently, the nasal spray demonstrated less variability in bioavailability than rectal gel (percentage of geometric coefficient of variation of area under the curve = 42%–66% for diazepam nasal spray compared with 87%–172% for rectal gel). The diazepam nasal spray safety profile is consistent with that expected for rectal diazepam, with low rates of nasal discomfort (≤6%). To further improve the efficacy of rescue therapy, investigation of novel intranasal benzodiazepine formulations is underway.